Biomimetic Materials with Multiple Protective Functionalities. (10th May 2019) - Liu, Zenghe; Zhang, Luzhi; Guan, Qingbao; Guo, Yifan; Lou, Jiaming; Lei, Dong; Wang, Shuliang; Chen, Shuo; Sun, Lijie; Xuan, Huixia; Jeffries, Eric Meade; He, Chuanglong; et al.
Abstract: Natural tissues possess superior material properties such as self‐healing, mechanical robustness, and mechanical gradients that allow organisms to adapt and survive in dangerous environments. Although highly desired, imparting synthetic materials with these biomimetic protective features remains a challenge. Here, the versatile dimethylglyoxime–urethane (DOU) moiety is used to create a multifunctional polyurethane (DOU‐PU). The reactivities of DOU including reversible dissociation, metal coordination, photolysis enabled self‐healing, high strength and toughness, mechanical gradient formation, and spatially controlled functionalization. By incorporating DOU, a multifunctional protective film is produced with superior resistance to mechanical damage, rapid room temperature self‐healing, and anti‐counterfeiting features. This super biomimetic film is expected to be very useful for the protection of various types of valuable objects such as electronics, diplomas, currency, and automobiles. Abstract : A versatile dimethylglyoxime–urethane moiety (DOU) is proposed to construct multifunctional protective materials. The reversible dissociation, metal coordination, and photolysis of the DOU enable dynamic bonds, dual‐hard phases, mechanical gradients, and spatially controlled functionalization. Accordingly, a multifunctional super protective film combining rapid room‐temperature self‐healing, mechanical robustness, and anti‐counterfeiting property is readily produced. It is expected to be very useful for protecting various valuable objects.